2019
DOI: 10.1016/j.isci.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-Permeant Mimetic of NMN Activates SARM1 to Produce Cyclic ADP-Ribose and Induce Non-apoptotic Cell Death

Abstract: Summary SARM1, an NAD-utilizing enzyme, regulates axonal degeneration. We show that CZ-48, a cell-permeant mimetic of NMN, activated SARM1 in vitro and in cellulo to cyclize NAD and produce a Ca 2+ messenger, cADPR, with similar efficiency as NMN. Knockout of NMN-adenylyltransferase elevated cellular NMN and activated SARM1 to produce cADPR, confirming NMN was its endogenous activator. Determinants for the activating effects and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
256
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(284 citation statements)
references
References 68 publications
20
256
0
Order By: Relevance
“…We next sought to determine the molecular mechanisms required for retinal degeneration in the NMNAT1-deficient retina. The loss of NMNAT2 induces an increase in NMN that is hypothesized to activate SARM1-dependent axon degeneration 53,54 . Our metabolomic analysis revealed that NMN is increased in the NMNAT1-deficient retinas ( Figure 1D), and previous studies have detected SARM1 in mouse and bovine photoreceptor cells [55][56][57] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next sought to determine the molecular mechanisms required for retinal degeneration in the NMNAT1-deficient retina. The loss of NMNAT2 induces an increase in NMN that is hypothesized to activate SARM1-dependent axon degeneration 53,54 . Our metabolomic analysis revealed that NMN is increased in the NMNAT1-deficient retinas ( Figure 1D), and previous studies have detected SARM1 in mouse and bovine photoreceptor cells [55][56][57] .…”
Section: Resultsmentioning
confidence: 99%
“…NMNAT enzymes inhibit the activation of SARM1 30 , potentially by consuming the NAD + precursor NMN, which is postulated to activate SARM1 53,54 . Prior to our study, loss of NMNAT2 was the only known trigger of SARM1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…SAM domains that mediate constitutive homomultimerization, and an executioner TIR domain (12). Upon injury, N-terminal inhibition is relieved, potentially via a rise in nicotinamide mononucleotide (NMN) secondary to NMN adenylyltransferase 2 (NMNAT2) loss (13)(14)(15), which thereby activates the intrinsic SARM1 TIR NADase (12,16). Active SARM1 cleaves the metabolic cofactor nicotinamide adenine dinucleotide (NAD+), generating nicotinamide and the calcium-mobilizing agents ADPR and cADPR (16), leading to local NAD + depletion, followed by metabolic collapse and axon fragmentation (17).…”
Section: Introductionmentioning
confidence: 99%
“…Its activation triggered axon degeneration locally and induced NAD depletion (89), suggesting that it may have NAD-hydrolyzing activity. Consistently, the Toll/interleukin-1 receptor (TIR) domain of SARM1, recombinantly produced and purified, was shown to be an effective NADase (87,88). Surprisingly, analysis of its hydrolysis products by HPLC showed, in addition to ADP-ribose, a small peak corresponding to cADPR (87, 88).…”
Section: A New Enzyme Emergesmentioning
confidence: 98%
“…It is thus surprising that sterile ␣ and Toll/interleukin-1 receptor motif-containing 1 (SARM1), a protein unrelated to and having no sequence similarity with CD38, has recently been shown to be able to catalyze the synthesis of cADPR (87,88). This unexpected discovery is a convergence of two different and independent lines of investigation.…”
Section: A New Enzyme Emergesmentioning
confidence: 99%